Highly selective transport of palladium from electroplating wastewater using emulsion liquid membrane process - Noah, N. F. M. (Taiwan Institute of Chemical Engineers, 2016)
A new liquid membrane formulation containing phosphinic acid groups as a carrier was developed for the selective extraction of palladium (Pd) from electroplating wastewater using emulsion liquid membrane (ELM) process. The important parameters that affect the membrane stability and the recovery of Pd were investigated, such as extraction time, concentrations of carrier and stripping agents, pH of feed phase, and treat ratio. Furthermore, at the optimum condition, the performance of Pd extraction was evaluated using real matrices solution. All experiments were carried out using batch extraction process and the recovery stage at high voltage demulsifier was employed. The results showed that the favorable conditions obtained for the extraction and the recovery processes were at 0.2M of Cyanex 302, 1.0M thiourea in 1.0M H2SO4 of stripping agent, 1:3 treat ratio, pH 3 of feed phase, and 5mins of extraction time. At these conditions, the maximum extraction and recovery of the Pd was 97% and 40%, respectively. Moreover, the result from the real matrices showed that almost 100% of Pd was extracted selectively over chromium at these conditions.